2021
DOI: 10.3390/microorganisms9020423
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Two Lytic Bacteriophages Infecting a Multi-Drug Resistant Salmonella Typhimurium and Their Efficacy to Combat Salmonellosis in Ready-to-Use Foods

Abstract: Foodborne salmonellosis is a global threat to public health. In the current study, we describe the isolation and characterization of two broad-spectrum, lytic Salmonella phages: SPHG1 and SPHG3 infecting a multidrug-resistant Salmonella Typhimurium EG.SmT3. Electron microscopy and whole genome analysis identified SPHG1 as a Myovirus, while SPHG3 as a new member of the genus “Kuttervirus” within the family Ackermannviridae. SPHG1 and SPHG3 had a lysis time of 60 min. with burst sizes of 104 and 138 PFU/cell, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 94 publications
2
46
0
2
Order By: Relevance
“…In this study, we found that UPWr_S1, UPWr_S3, and UPWr_S4 phages alone and the UPWr_S134 phage cocktail exhibited a great ability to decrease the number of Salmonella from biofilm structures in a 96-well microtiter plate and on stainless steel washers formed by strong and moderate biofilm producers, S. Enteritidis ATCC 13076 and 372 lux strains, respectively. A previous study on S. Typhimurium and S. Enteritidis showed significant biofilm eradication by phage cocktail at titers of 7 log 10 and 8 log 10 PFU/mL in a 96-well microplate with the reduction levels varying between 44 and 63% (Gong and Jiang, 2017;Islam et al, 2019;Esmael et al, 2021). The ability of UPWr_S1, UPWr_S3, and UPWr_S4 phages and the UPWr_S134 phage cocktail to eliminate bacteria from biofilm formed by S. Enteritidis 372 lux corresponds to the average reduction level of most Salmonella-targeting phage cocktails, whereas monophage and phage cocktail treatment of biofilm formed by the strong biofilm producer S. Enteritidis ATCC 13076 resulted in almost complete biofilm eradication.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, we found that UPWr_S1, UPWr_S3, and UPWr_S4 phages alone and the UPWr_S134 phage cocktail exhibited a great ability to decrease the number of Salmonella from biofilm structures in a 96-well microtiter plate and on stainless steel washers formed by strong and moderate biofilm producers, S. Enteritidis ATCC 13076 and 372 lux strains, respectively. A previous study on S. Typhimurium and S. Enteritidis showed significant biofilm eradication by phage cocktail at titers of 7 log 10 and 8 log 10 PFU/mL in a 96-well microplate with the reduction levels varying between 44 and 63% (Gong and Jiang, 2017;Islam et al, 2019;Esmael et al, 2021). The ability of UPWr_S1, UPWr_S3, and UPWr_S4 phages and the UPWr_S134 phage cocktail to eliminate bacteria from biofilm formed by S. Enteritidis 372 lux corresponds to the average reduction level of most Salmonella-targeting phage cocktails, whereas monophage and phage cocktail treatment of biofilm formed by the strong biofilm producer S. Enteritidis ATCC 13076 resulted in almost complete biofilm eradication.…”
Section: Discussionmentioning
confidence: 87%
“…EOP was calculated through the previously reported method ( Khawaja et al, 2016 ) using SG-C as a reference strain. EOP values from 0.5 to 1 were classified as highly efficient, values between 0.2 to < 0.5 as moderately efficient and 0.0001 to < 0.2 as least efficient while < 0.0001 as in-efficient ( Mirzaei and Nilsson, 2015 ; Esmael et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This is important as there are different temperatures in the food chain and this study would indicate that phage treatment could be used over a wide temperature range. In the same way, Esmael et al [114] tested to S. Typhimurium lytic phages against 72 h-old biofilms formed in microtiter plates. Concentrations of 8 log10 PFU/mL reduced more than three times biofilm formation.…”
Section: Applied Studies On Salmonella Biofilmsmentioning
confidence: 99%